Mutual influence of ants and aphidophages on the biology and ecology of aphids in apple orchards in southern Russia - I. V. Balakhnina; O. Yu. Kremneva; I. B. Popov; A. Yu. Nesterova; E. G. Snesareva (Юг России: экология, развитие)
The aim was to study the relationships between colonies of different species of apple aphids with two species of ants and some aphidophages in the south of Russia.The studies were carried out from 2013 to 2020 in the apple orchards of the Kuban educational farm of the Kuban State Agrarian University in Krasnodar. The area of the two experimental plots was 0.5 hectares each. The objects of the studies were four species of aphids: Aphis pomi, Dysaphis devecta, Dysaphis plantaginea and Eriosoma lanigerum. Monitoring was carried out every seven days during the entire apple tree growing season: aphids were noted as individuals and colonies, as were various species of aphidophages.Data were obtained showing that predator-prey relationships may change depending on the presence or absence of ants. The main types of aphidophages were identified in all four species of aphids observed: Aphis pomi – 13 species, Dysaphis devecta – 4 species, Dysaphis plantaginea – 7 species, Aphis pomi – 1 species. The dependence of the increase in green apple aphid colonies on the number of ants was shown.The most preferred species for various aphidophages is the green apple aphid. In April-March, ants often begin feeding in Dysaphis devecta colonies, but then move on to Aphis pomi. The results of the study can be used in planning protective measures in apple orchards.